Growing Character Through Wisdom of Heart: Implementation of Sufi Education Integration in Student Character Development - Muhlison, Muhlison (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study examines the implementation of the integration of sufistic education in the formation of students' character with a sufistic educational approach, which focuses on the development of spiritual, emotional, and moral aspects. Because most character education still focuses on cognitive and behavioral approaches without integrating spiritual approaches. This research uses a qualitative approach with a case study design carried out at Madrasah Aliyah Al-Ansor Padangsidimpuan. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation studies of learning activities and sufistic-based character strengthening programs. The research informants consisted of teachers, students, and principals who were selected purposively. The data obtained was analyzed thematically through the process of data reduction, data presentation, and conclusion drawn, with data validity tests carried out through triangulation of sources and techniques. This study found that the integration of sufistic values using the methods of takhalli (self-cleansing), tahalli (filling oneself with positive values), and tajalli (manifestation of spiritual values in action) can improve the quality of students' character. The implication of this study is the importance of integrating sufistic value-based character education in the educational curriculum.